COMPARISON OF THREE DISTINCT PROPHYLACTIC AGENTS AGAINST INVASIVE FUNGAL INFECTIONS IN PATIENTS UNDERGOING HAPLO-IDENTICAL HEMATOPOIETIC STEM CELL TRANSPLANTATION AND POST-TRANSPLANT CYCLOPHOSPHAMIDE - Jean Elcheikh (Mediterranean Journal of Hematology and Infectious Diseases)
Over the past decade, invasive fungal infections (IFI) have remained an important problem in patients undergoing allogeneic haematopoietic stem cell transplantation (Allo-HSCT). The optimal approach for prophylactic antifungal therapy has yet to be determined.